Teaching preservice teachers the Teaching Games for Understanding approach: A proposed PETE program - Chatoupis, Constantine (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2017)
Teaching Games for Understanding (TGfU) is a curriculum model that empasizes a tactical approach to teaching games. Over the last decade there has been an international consensus on the need to incorporate this model into Physical Education Teacher Education (PETE) programs. The present paper proposes a PETE program that employs TGfU as conceptual framework to encourage preservice teachers to use it for teaching games and sports at schools. Combining theory, observation of demonstration, practice, and feedback under protected conditions and in real school settings, the proposed program provides preservice teachers with adequate opportunities to develop familiarity and confidence with TGfU as well as to experience success in using it. A number of courses that are part of a PETE program, courses in which TGfU is integrated, are presented.